Optimization of treatment for patients with combined unstable pelvic and thoracic injuries - О.А. Бур’янов; В.П. Кваша; В.М. Дьомін; Д.В. Мясніков; В.М. Лянскорунський (Медицина неотложных состояний, 2024)
Background. In patients with polytrauma, damage to the pelvis and chest organs occurs in 21.2–45.7 % of cases. Thoracic trauma, one of the most frequent localizations in multiple injuries, is found in 50–80 % of patients and is of significant importance for the prognosis of the victim’s life. Clinical studies indicate that an average of 20 % of all fatal outcomes in polytrauma are due to chest trauma. Isolated chest and pelvic injuries are serious injuries themselves, and their combination, taking into account the mutual aggravation symptom, is an urgent issue of modern orthopedics and traumatology. Its solution requires a multidisciplinary approach, and further study will allow to refine treatment strategies and improve outcomes. The purpose was to improve treatment outcomes in patients with combined injuries of the pelvis and chest by optimizing treatment algorithm. Materials and methods. The clinical study is based on the examination and treatment of 36 patients with combined chest and pelvic injuries from 2014 to 2023. The average age of the patients was 41.4 ± 16.3 years. Results. Combined injuries of the pelvis and chest lead to a severe condition of patients according to the Injury Severity Score and Trauma Score. Stable fixation in type B pelvic fractures is provided by an external fixation device, while in type C fractures, stabilization of the posterior pelvic ring is mandatory. Rib osteosynthesis performed by certain indications is a more effective approach compared to non-surgical treatment, which allows to reduce the frequency of acute respiratory distress syndrome and pneumonia, the length of stay in the intensive care unit and the period of inpatient treatment. The overall mortality in the experimental group was 11.1 %. For patients who did not survive, the average Injury Severity Score was 40.3, the average Trauma Score was 5.4 ± 1.5 points. Conclusions. 1. For type B pelvic injuries, which are characterized by anterior, rotational and partially posterior instability, stabilization of the anterior part is sufficient. Type C injuries, which are characterized by anterior and posterior instability, require stabilization of the anterior and posterior pelvic rings. 2. Rib osteosynthesis performed by indications provides a lower incidence of acute respiratory distress syndrome and pneumonia, as well as a lower need for artificial lung ventilation and a shorter stay in the intensive care unit.